Aplikasi Catatan Penjualan Berbasis Web Menggunakan Kombinasi HTML5, CSS3, JavaScript, dan DBMS Innodb - Rizky Parlika; Yohanes Dimas Wisnu Wiratama; Benedictus Rafael Lesmana; Radja Aulia Edward; Dasilva, Mortekiano Nigel (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2022)
Store sales recording activity is an important thing. By record the sell, the seller can minimize errors in calculating profit and loss due to items that are not recorded. The seller also compares number of each product which sold at a time and can make plans to plan the next sales strategy. By adopting the ADDIE method which in its stages goes through Analyze, Design, Development & Implementation, and Evaluation phases, the author develops a store sales recording application that has CRUD (Create, Read, Update, Delete) as the main feature of number of sales recording compiled with a MySQL database. Bar charts and pie charts are displayed as a visualization of product sales data using Bootstrap.